From nomadism to monarchy? revisiting the early Iron Age southern Levant - Annual Aharoni Symposium 2017 Tel Aviv; Ḳokh, ʿIdo 1981-; Lipshits, ʿOded 1963-; Sergi, Omer 1977-; Arie, Eran (Tel Aviv Emery and Clare Yass Publications in Archaeology, The Institute of Archaeology, Tel Aviv University, 2023)
Archaeological exploration in the Central Highlands of the Southern Levant conducted during the 1970s and 1980s dramatically transformed the scholarly understanding of the early Iron Age and led to the publication of From Nomadism to Monarchy: Archaeological and Historical Aspects of Early Israel, by Israel Finkelstein and Nadav Na'aman. This volume explores and reassesses the legacy of that foundational text. Using current theoretical frameworks and taking into account new excavation data and methodologies from the natural sciences, the seventeen essays in this volume examine the archaeology of the Southern Levant during the early Iron Age and the ways in which the period may be reflected in biblical accounts. The variety of methodologies employed and the historical narratives presented within these contributions illuminate the multifaceted nature of contemporary research on this formative period.Building upon Finkelstein and Na'aman's seminal study, this work provides an essential update. It will be welcomed by ancient historians, scholars of early Israel and the early Iron Age Southern Levant, and biblical scholars. In addition to the editors, the contributors to this volume are Eran Arie, Erez Ben-Yosef, Cynthia Edenburg, Israel Finkelstein, Yuval Gadot, Assaf Kleiman, Gunnar Lehmann, Defna Langgut, Aren M. Maeir, Nadav Na'aman, Thomas Römer, Lidar Sapir-Hen, Katja Soennecken, Dieter Vieweger, Ido Wachtel, and Naama Yahalom-Mack
In English
Keywords: SOCIAL SCIENCE / Archaeology; biblical accounts; central highlands of the Southern Levant; iron age archaeology; update to From Nomadism to Monarchy: Archaeological and Historical Aspects of Early Israel; Konferenzschrift -- 2017 -- Tel Aviv